Design of Steel Reheating Furnace Gas Actuator Control System Using Arduino UNO - Rizdam Firly Muzakki; Chairul Gagarin Irianto (Universitas Medan Area, 2022)
To minimize production down time that caused by equipment damage, it is necessary to have sufficient spare part availability. But sometimes this is hard to fulfill because of the price of spare parts and there are any specifications that are difficult to find. One of the equipment that has a vital role in steel manufacturing process is a gas valve actuator that has a function to regulate the flow of gas volume used in the billet reheating process. Most actuator problems are caused by the control circuit, while the mechanical and actuating devices can still work normally. Replacing the actuator unit will require a large cost, as well as a relatively long response time. From these problems, a control system is designed that can be applied to the actuator units that are already available by utilizing Arduino UNO as a processor, to reduce down time due to equipment damage. The method applied to this tool is to compare the input signal value with the actual gas valve opening position from the potentiometer. Based on the results of data collection shows this control system has an average error value of 0.7075%. The results of the tests carried out show that the Arduino UNO-based control system can operate the actuator unit effectively, to be used in the billet reheating process.